Netball Club Information System - Mohd Rabiol, Nur Izzati Amani; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2024)
Netball is a popular extracurricular activity that falls into the sports arena at the school. The school has formed a netball sports club to organise practises and competitions. All team and training-related data, along with other pertinent data, is processed manually using logbooks in some school. Due to the rapid advancement of technology and better database administration, a web-based information system is required to manage sports club information more effectively. The Netball Club Information System was created in this project to manage team information, training and scheduling, tournaments, and reporting. The SK Timbang Dayang Kota Belud Sabah co-curricular department is a project stakeholder. Teachers, administrators, and gamers are system users. Prototyping and coding using PHP and MySQL are used to develop the software. This proposed system will help this netball club organization in managing netball club information more systematically.